Socio-Economic Effects of Oil Exploration in Uganda: A Case Study of Buliisa District Western Uganda - Enosi Nyakairu (Uganda Christian University, 2024)
This study investigates the socio-economic effects of oil exploration in Buliisa District, Western Uganda. Employing a cross-sectional survey design with both quantitative and qualitative approaches, the research explores the impact of oil exploration on infrastructure development and employment opportunities within the district. The study population comprised municipality administrators, oil companies’ officials, area residents, local councils, and politicians. Using a sample size of 234 respondents, including area residents, local councils, oil company officials, municipality administrators, and politicians, data was collected and analyzed to draw meaningful insights. Results indicate a strong positive relationship between environmental effects and oil exploitation staff, suggesting an increase in staff involvement with rising environmental effects. However, a very weak positive correlation is observed between infrastructural development and oil exploitation, indicating limited impact of infrastructure on the success of oil projects. The findings also reveal a significant positive correlation between employment opportunities and oil exploitation, implying that increased opportunities in the industry enhance employment likelihood. Based on the conclusions drawn, practical recommendations are proposed. These include prioritizing environmental management practices to mitigate negative impacts, diversifying economic investments to reduce dependency on the oil sector, and implementing inclusive employment policies to ensure equitable access to job opportunities. These findings offer valuable insights for stakeholders aiming to enhance the socio-economic impact of oil exploration on Buliisa District and underscore the need for holistic strategies to maximize benefits while mitigating potential risks.